A kind of wear-resistant asphalt and preparation method thereof
By using multifunctional fibers and syringe-modified cellulose in asphalt, the shortcomings of ordinary asphalt in terms of wear resistance, deformation resistance, high temperature resistance and oxidation resistance are solved, and the service life of asphalt is significantly extended.
Patent Information
- Application Number
- CN202510086556.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-04
AI Technical Summary
Ordinary asphalt has shortcomings in wear resistance, deformation resistance, high temperature resistance and oxidation resistance, resulting in a short service life.
Multifunctional fibers and syringic acid modified cellulose are used to participate in the preparation of asphalt. By introducing epoxy groups and syringic acid structure, the resistance to deformation, high temperature and oxidation resistance of asphalt is enhanced.
It significantly improves the wear resistance, high temperature resistance, deformation resistance and oxidation resistance of asphalt, and extends the service life of asphalt.
Smart Images

Figure CN119752207A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt preparation, and in particular to a wear-resistant asphalt and a preparation method thereof. Background Art
[0002] Asphalt is a black and brownish black colloid, mainly composed of elements such as carbon, hydrogen, oxygen, nitrogen, and sulfur. It is a byproduct of petroleum and has viscosity, plasticity, hydrophobicity, and corrosion resistance. It is widely used in the field of road construction, and its performance directly affects the safety, comfort, and service life of the road. During the use of the road, it will be repeatedly crushed and rubbed by vehicles, and it is easily affected by environmental factors such as light and heat. In the high temperature environment in summer, ordinary asphalt is easily softened by heat, emitting an unpleasant odor and becoming sticky, which accelerates the aging process of asphalt roads, causing wear, deformation, peeling, and cracking, affecting driving comfort and posing a great safety hazard.
[0003] With the rapid development of road construction, modern transportation has higher and higher requirements for road materials. Ordinary asphalt has been difficult to meet the current use requirements in terms of wear resistance, high temperature resistance, aging resistance and deformation resistance. Therefore, when using it, people usually improve it. For example, the patent with publication number CN110437638B discloses an asphalt modifier, modified asphalt and asphalt modification method. The patent heats and melts the base asphalt, adds lobster shell powder, and manually stirs and shears to obtain lobster shell powder modified asphalt. The waste lobster shell powder can improve the rigidity of the asphalt binder, and improve the high temperature stability and creep resistance of the base asphalt. However, the patent does not improve the antioxidant capacity of asphalt, so the aging rate of this asphalt is fast and the service life is short. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant asphalt and a preparation method thereof, which solves the following technical problems: (1) the problem that ordinary asphalt has poor wear resistance and deformation resistance; (2) the high temperature resistance of ordinary asphalt needs to be improved, and its aging resistance is not strong, resulting in a short service life.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A wear-resistant asphalt comprises the following raw materials in parts by weight: 80-100 parts of base asphalt, 6-8 parts of maleic anhydride modified polypropylene, 10-12 parts of styrene-butadiene-styrene block copolymer, 5-6 parts of multifunctional fiber, 8-10 parts of syringic acid modified cellulose, 5-8 parts of silicon carbide, and 2-3 parts of coupling agent; the multifunctional fiber is prepared by introducing epoxy groups on the surface of medical stone fiber and then reacting with terminal amino polysiloxane; the syringic acid modified cellulose is prepared by reacting the carboxyl group in the syringic acid structure with the hydroxyl group in the cellulose structure.
[0006] Furthermore, the coupling agent is any one of a titanate coupling agent and a lignin coupling agent.
[0007] Furthermore, the preparation method of the multifunctional fiber comprises the following steps: S1: Place medical stone fiber in deionized water, ultrasonically disperse for 10-15 minutes, add 2,3-epoxypropyltrimethylammonium chloride, stir thoroughly for 8-12 hours, filter, wash, and dry to obtain epoxidized medical stone fiber; S2: placing the epoxidized medical stone fiber in toluene, adding amino-terminated polysiloxane, heating to react, filtering, washing and drying to obtain the multifunctional fiber.
[0008] In this scheme, 2,3-epoxypropyltrimethylammonium chloride carries a positive charge in an aqueous solution and can produce an adsorption effect on the surface of medical stone fiber, and epoxy groups are introduced on its surface to obtain epoxidized medical stone fiber. The epoxy groups on the surface of the epoxidized medical stone fiber can then undergo a ring-opening reaction with the amino groups in the amino-terminated polysiloxane structure to obtain a multifunctional fiber. The multifunctional fiber surface has multiple hydroxyl groups that can participate in the preparation process of asphalt, interact with the asphalt base material, form a network structure, and enhance the deformation resistance of asphalt. At the same time, the polysiloxane structure coated on its surface has multiple silicon-oxygen bonds and has good thermal stability, which can effectively enhance the high temperature resistance of asphalt and effectively prevent the asphalt from becoming sticky at high temperatures. At the same time, the multifunctional fiber uses medical stone fiber as a matrix. As an inorganic fiber, medical stone fiber can enhance the wear resistance of asphalt, and can also generate tensile stress with the asphalt base material to further enhance the deformation resistance of asphalt.
[0009] Furthermore, in step S1, the diameter of the medical stone fiber is 8-12 μm and the length is 5-12 mm.
[0010] Furthermore, in step S2, the temperature of the temperature-raising reaction is 70-80° C. and the time is 3-5 hours.
[0011] Furthermore, the preparation method of the syringic acid-modified cellulose comprises the following steps: Place carboxymethyl cellulose in N,N-dimethylformamide, mix and stir thoroughly, add syringic acid and a catalyst, heat to 90-95°C and react for 5-6 hours, collect the product after reduced pressure distillation, and obtain syringic acid-modified cellulose.
[0012] In this scheme, under the action of a catalyst, the hydroxyl groups in the carboxymethyl cellulose structure and the carboxyl groups in the syringic acid structure undergo an esterification reaction to obtain syringic acid-modified cellulose. The syringic acid-modified cellulose structure has multiple hydroxyl groups that can interact with the asphalt matrix material, effectively improving the density of the asphalt matrix material, and enhancing the wear resistance and stability of the asphalt matrix material. At the same time, the syringic acid in its structure can terminate the free radical chain reaction, reduce the oxidative degradation of asphalt, and effectively improve the antioxidant capacity of asphalt. The small molecule syringic acid is combined with the carboxymethyl cellulose macromolecule in a chemically bonded manner, which can effectively protect and anchor the syringic acid, prevent the migration of syringic acid during long-term use, and is not easy to fail, exerting a longer-lasting antioxidant capacity, greatly improving the service life of asphalt.
[0013] Furthermore, the catalyst is p-toluenesulfonic acid.
[0014] A method for preparing wear-resistant asphalt comprises the following steps: Step 1: Mix base asphalt, maleic anhydride modified polypropylene, and styrene-butadiene-styrene block copolymer, heat and stir to obtain an asphalt base material; Step 2: Add multifunctional fiber, syringic acid-modified cellulose, silicon carbide, and a coupling agent to the asphalt base material, heat up and stir, and collect the product to obtain asphalt.
[0015] Furthermore, in step 1, the temperature of the heating and stirring is 180-190° C., and the time is 1.5-2 h.
[0016] Furthermore, in step 2, the temperature of the heating and stirring is 160-170° C., and the time is 2-3 hours.
[0017] Beneficial effects of the present invention: The present invention involves multifunctional fiber and syringic acid-modified cellulose in the asphalt preparation process, so that the prepared asphalt has excellent wear resistance, high temperature resistance, deformation resistance and oxidation resistance, and has a very long service life.
[0018] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1The present invention is a flow chart of the preparation process of the wear-resistant asphalt. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The preparation methods of the multifunctional fibers and syringic acid-modified cellulose in the following examples and comparative examples of the present invention are as follows: 1. Preparation of multifunctional fibers S1: Place 3g of medical stone fiber with a diameter of 8μm and a length of 5mm in 100ml of deionized water, ultrasonically disperse for 10min, add 3.2g of 2,3-epoxypropyltrimethylammonium chloride, stir well for 8-12h, filter, wash, and dry to obtain epoxidized medical stone fiber; S2: 3.5 g of epoxidized medical stone fiber was placed in 120 ml of toluene, 3.6 g of amino-terminated polysiloxane was added, the temperature was raised to 70°C for reaction for 3 h, and the multifunctional fiber was obtained after filtering, washing and drying.
[0023] Through the above technical scheme, 2,3-epoxypropyltrimethylammonium chloride carries a positive charge in the solution, and can combine with the negatively charged hydroxyl groups on the surface of the medical stone fiber to generate electrostatic attraction, thereby introducing epoxy groups into the surface of the medical stone fiber. Then, a ring-opening reaction occurs between the epoxy groups and the amino groups in the amino-terminated polysiloxane structure to obtain multifunctional fibers. This multifunctional fiber is involved in the preparation process of the asphalt base material, so that the prepared asphalt has good toughness and high temperature and wear resistance, which can meet the current road construction requirements.
[0024] 2. Preparation of syringic acid modified cellulose 2.6 g of carboxymethyl cellulose was placed in 60 ml of N,N-dimethylformamide, and after sufficient mixing and stirring, 2 g of syringic acid and 0.6 g of p-toluenesulfonic acid were added, and the temperature was raised to 90°C for reaction for 5 h. The product was collected after reduced pressure distillation to obtain syringic acid-modified cellulose.
[0025] Through the above technical scheme, under the catalytic action of p-toluenesulfonic acid, the hydroxyl groups in the carboxymethyl cellulose structure react with the carboxyl groups in the syringic acid structure to undergo esterification reaction to obtain syringic acid-modified cellulose, and the small molecule antioxidant syringic acid is introduced into the polymer segment of the carboxymethyl cellulose in a chemically bonded manner, and the polymer segment structure has hydroxyl groups and can interact with the asphalt base material, thereby coating the small molecule antioxidant syringic acid, protecting it and anchoring it, so that it can exert its antioxidant ability for a long time, effectively preventing asphalt oxidation, and greatly extending the service life of asphalt. Example 1
[0026] Asphalt preparation Step 1: Mix 80 parts of base asphalt, 6 parts of maleic anhydride modified polypropylene, and 10 parts of styrene-butadiene-styrene block copolymer, heat to 180°C, and stir continuously for 1.5 hours to obtain an asphalt base material; Step 2: Add 5 parts of multifunctional fiber, 8 parts of syringic acid-modified cellulose, 5 parts of silicon carbide, and 2 parts of titanate coupling agent to the asphalt base material, heat to 160° C., stir thoroughly for 2 hours, and collect the product to obtain asphalt. Example 2
[0027] Asphalt preparation Step 1: Mix 90 parts of base asphalt, 7 parts of maleic anhydride modified polypropylene, and 11 parts of styrene-butadiene-styrene block copolymer, heat to 185°C, and stir continuously for 1.8 hours to obtain an asphalt base material; Step 2: Add 5.5 parts of multifunctional fiber, 9 parts of syringic acid-modified cellulose, 6 parts of silicon carbide, and 2.5 parts of titanate coupling agent to the asphalt base material, heat to 165° C., stir thoroughly for 2.5 hours, and collect the product to obtain asphalt. Example 3
[0028] Asphalt preparation Step 1: Mix 100 parts of base asphalt, 8 parts of maleic anhydride modified polypropylene, and 12 parts of styrene-butadiene-styrene block copolymer, heat to 190°C, and stir continuously for 2 hours to obtain an asphalt base material; Step 2: Add 6 parts of multifunctional fiber, 10 parts of syringic acid-modified cellulose, 8 parts of silicon carbide, and 3 parts of lignin coupling agent to the asphalt base material, heat to 170° C., stir thoroughly for 3 hours, and collect the product to obtain asphalt.
[0029] Comparative Example 1 Asphalt preparation Step 1: Mix 90 parts of base asphalt, 7 parts of maleic anhydride modified polypropylene, and 11 parts of styrene-butadiene-styrene block copolymer, heat to 185°C, and stir continuously for 1.8 hours to obtain an asphalt base material; Step 2: Add 9 parts of syringic acid-modified cellulose, 6 parts of silicon carbide, and 2.5 parts of titanate coupling agent to the asphalt base material, heat to 165° C., stir thoroughly for 2.5 hours, and collect the product to obtain asphalt.
[0030] Comparative Example 2 Asphalt preparation Step 1: Mix 90 parts of base asphalt, 7 parts of maleic anhydride modified polypropylene, and 11 parts of styrene-butadiene-styrene block copolymer, heat to 185°C, and stir continuously for 1.8 hours to obtain an asphalt base material; Step 2: Add 5.5 parts of multifunctional fiber, 6 parts of silicon carbide, and 2.5 parts of titanate coupling agent to the asphalt base material, raise the temperature to 165° C., stir thoroughly for 2.5 hours, and collect the product to obtain asphalt.
[0031] Comparative Example 3 Asphalt preparation Step 1: Mix 90 parts of base asphalt, 7 parts of maleic anhydride modified polypropylene, and 11 parts of styrene-butadiene-styrene block copolymer, heat to 185°C, and stir continuously for 1.8 hours to obtain an asphalt base material; Step 2: Add 5.5 parts of epoxidized medical stone fiber, 9 parts of cellulose modified with syringic acid, 6 parts of silicon carbide, and 2.5 parts of titanate coupling agent to the asphalt base material, heat to 165°C, stir thoroughly for 2.5 hours, and collect the product to obtain asphalt.
[0032] Comparative Example 4 Asphalt preparation Step 1: Mix 90 parts of base asphalt, 7 parts of maleic anhydride modified polypropylene, and 11 parts of styrene-butadiene-styrene block copolymer, heat to 185°C, and stir continuously for 1.8 hours to obtain an asphalt base material; Step 2: Add 5.5 parts of multifunctional fiber, 9 parts of carboxymethyl cellulose, 6 parts of silicon carbide, and 2.5 parts of titanate coupling agent to the asphalt base material, heat to 165°C, stir thoroughly for 2.5 hours, and collect the product to obtain asphalt.
[0033] Performance Testing The asphalt prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4 was made into samples that met the specifications. The softening point of the samples was tested by the ring and ball method with reference to the standard GB / T4507-2014 to determine the high temperature resistance of the samples. The ductility of the samples was tested with reference to the standard GB / T4508-2010 to determine the deformation resistance of the samples. The samples and the samples treated in an aging box at 80°C for 48 hours were subjected to wear tests using an Akron abrasion machine. The wear value was calculated using the following formula: wear value = sample mass before wear - sample mass after wear. The smaller the wear value, the better the wear resistance of the sample. The specific test results are shown in the table below:
[0034] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent high temperature resistance, deformation resistance, wear resistance and aging resistance. In the sample prepared in Comparative Example 1, no multifunctional fiber was added, and the sample's deformation resistance and high temperature resistance were poor. In the sample prepared in Comparative Example 2, no syringic acid-modified cellulose was added, and the aging resistance was poor. In the sample prepared in Comparative Example 3, epoxidized medical stone fiber was directly added, and the surface was not coated with terminal amino polysiloxane, so the high temperature resistance needs to be improved. In the sample prepared in Comparative Example 4, carboxymethyl cellulose was directly added, and it was not modified by syringic acid, and the aging resistance of the sample was poor.
[0035] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0036] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A wear-resistant asphalt, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of matrix asphalt, 6-8 parts of maleic anhydride modified polypropylene, 10-12 parts of styrene-butadiene-styrene block copolymer, 5-6 parts of multifunctional fiber, 8-10 parts of syringic acid modified cellulose, 5-8 parts of silicon carbide, and 2-3 parts of coupling agent; the multifunctional fiber is prepared by introducing epoxy groups on the surface of medical stone fiber and then reacting with terminal amino polysiloxane; the syringic acid modified cellulose is prepared by reacting the carboxyl group in the syringic acid structure with the hydroxyl group in the cellulose structure.
2. The wear-resistant asphalt according to claim 1, characterized in that: The coupling agent is any one of a titanate coupling agent and a lignin coupling agent.
3. The wear-resistant asphalt according to claim 1, characterized in that: The preparation method of the multifunctional fiber comprises the following steps: S1: Place medical stone fiber in deionized water, ultrasonically disperse for 10-15 minutes, add 2,3-epoxypropyltrimethylammonium chloride, stir thoroughly for 8-12 hours, filter, wash, and dry to obtain epoxidized medical stone fiber; S2: placing the epoxidized medical stone fiber in toluene, adding amino-terminated polysiloxane, heating to react, filtering, washing and drying to obtain the multifunctional fiber.
4. The wear-resistant asphalt according to claim 3, characterized in that: In step S1, the diameter of the medical stone fiber is 8-12 μm and the length is 5-12 mm.
5. The wear-resistant asphalt according to claim 3, characterized in that: In step S2, the temperature of the temperature-raising reaction is 70-80° C. and the time is 3-5 hours.
6. The wear-resistant asphalt according to claim 1, characterized in that: The preparation method of the syringic acid modified cellulose comprises the following steps: Place carboxymethyl cellulose in N,N-dimethylformamide, mix and stir thoroughly, add syringic acid and a catalyst, heat to 90-95°C and react for 5-6 hours, collect the product after reduced pressure distillation, and obtain syringic acid-modified cellulose.
7. The wear-resistant asphalt according to claim 6, characterized in that: The catalyst is p-toluenesulfonic acid.
8. A method for preparing wear-resistant asphalt as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Mix base asphalt, maleic anhydride modified polypropylene, and styrene-butadiene-styrene block copolymer, heat and stir to obtain an asphalt base material; Step 2: Add multifunctional fiber, syringic acid-modified cellulose, silicon carbide and a coupling agent to the asphalt base material, heat up and stir, and collect the product to obtain asphalt.
9. The method for preparing wear-resistant asphalt according to claim 8, characterized in that: In step 1, the temperature of the heating and stirring is 180-190° C., and the time is 1.5-2 h.
10. The method for preparing wear-resistant asphalt according to claim 8, characterized in that: In step 2, the temperature of the heating and stirring is 160-170° C., and the time is 2-3 hours.
Citation Information
Patent Citations
An asphalt modifier, modified asphalt, and a method for modifying asphalt.
CN110437638B
Cited By
Treating agent for surface corrosion prevention of zinc-aluminum-magnesium alloy and preparation method of treating agent
CN121851849A